The human term and its synonymous designations between Al-Raghib Al-Isfahani (502 A.H) And Al-Sabzwari (1414 A.H): Semantic study in Quranic vocabulary - AlJayashi, Talib; AlArnaouti, Iyad (Al-Adab Journal, 2023)
This research is concerned with the singular indication of man, the origin of his creation and upbringing, and the names related to him. Since the creation of man is considered a miracle, like the miracle of the creation of the heavens and the earth, and what is in them and what is between them. God Almighty did not create him as an abstract mind only, nor a luminous spirit, nor a soul, nor a body on his own, but rather he created him as a body, spirit, soul, and mind. So he defined for him the frameworks of thinking and conscience, and showed him the limits of his body and the controls of his mind and soul, so he proceeded with all this to think, eat, love and hate, and distinguish the bad from the good, and made him aware of the secrets of the body and the power in it that moves it or stops it if he wants to. Hence the discourse of the Holy Qur’an about the mind that thinks, and about the soul to reveal its impulses and whims, so it guides it to the right path, and warns it not to slip into the quagmire of its misleading whims, about the members of the body; To control the power that God Almighty entrusted him with. The Holy Qur’an has detailed how man was created and the stages that this great creation went through. To be the focus of other beings that God Almighty has subjected to him, and the Holy Qur’an mentioned it in many terms, some of which are specific, and some are general, benefiting the individual at times and benefiting the entire human society, male and female at other times, The meanings of these terms were distributed to include man in his physical, sensual and non-sensual condition.